2013
DOI: 10.1371/journal.pone.0076785
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Regulates Osteoblast Function by Focal Adhesion Kinase Signaling in the Process of Fracture Healing

Abstract: Several biological studies have indicated that hedgehog signaling plays an important role in osteoblast proliferation and differentiation, and sonic hedgehog (SHH) expression is positively correlated with phosphorylated focal adhesion kinase (FAK) Tyr397. However, the relationship between them and their role in the process of normal fracture repair has not been clarified yet. Immunohistochemical analysis revealed that SHH and pFAK Tyr397 were expressed in bone marrow cells and that pFAK Tyr397 was also detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
(54 reference statements)
0
43
0
Order By: Relevance
“…), 5′‐TTCTCCAACCCACGAATGCAC‐3′ and 5′‐CAGGTACGTGTGGTAGTGAGT‐3′ forward and reverse primers for Runx2 (Horikiri et al . ), 5′‐AATGGTGCTCCTGGTATTGC‐3′ and 5′‐ GGCACCAGTGTCTCCTTTGT‐3′ forward and reverse primers for COL1 (Alford et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), 5′‐TTCTCCAACCCACGAATGCAC‐3′ and 5′‐CAGGTACGTGTGGTAGTGAGT‐3′ forward and reverse primers for Runx2 (Horikiri et al . ), 5′‐AATGGTGCTCCTGGTATTGC‐3′ and 5′‐ GGCACCAGTGTCTCCTTTGT‐3′ forward and reverse primers for COL1 (Alford et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression levels of ALP, OC, Runx2 and COL1 were measured using real-time PCR. Primer sequences were 5 0 -AACCCAGACACAAGCATTCC 3 0 and 5 0 -GCCTTTGAGGTTTTTGGTCA-3 0 forward and reverse primers for ALP (Negishi-Koga et al 2011), 5 0 -CGCTCTGTCTCTCTGACCTC-3 0 and 5 0 -TCACAAG CAGGGTTAAGCTC-3 0 forward and reverse primers for OC (Alford et al 2010), 5 0 -TTCTCCAACCCACGAATG CAC-3 0 and 5 0 -CAGGTACGTGTGGTAGTGAGT-3 0 forward and reverse primers for Runx2 (Horikiri et al 2013), 5 0 -AATGGTGCTCCTGGTATTGC-3 0 and 5 0 -GGCACCAGTGTCTCCTTTGT-3 0 forward and reverse primers for COL1 (Alford et al 2010).…”
Section: Osteogenic-related Gene Expression Analysis By Real-time Pcrmentioning
confidence: 99%
“…The right eighth rib of each experimental animal was fractured as previously described [10]. Briefly, each experimental animal was anesthetized, and the eighth rib on the right side was exposed and cut vertical to the axis with scissors.…”
Section: Fracture Experimentsmentioning
confidence: 99%
“…In general, Shh acts in the early stages of development to regulate patterning and growth [9]. Recently, several studies reported that Shh might be related to fracture healing [10,11]. Following the inactivation of HH signaling, the activity of Smo is inhibited by a receptor known as Patched (Ptch).…”
Section: Introductionmentioning
confidence: 99%
“…Mandible bone healing after IVRO could be associated with normal bone development, including not only cartilage and bone formation, but also endochondral resorption and bone remodeling. According to a previous in vitro study, chondrocytes are remodeled and bone remodeling is started 6 weeks after fracture [18], [19]. The effect of the estrogen inhibitor tamoxifen should be further explored in clinical studies.…”
Section: Discussionmentioning
confidence: 99%